2023
DOI: 10.21203/rs.3.rs-2038495/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Automated western blot analysis of ototoxin-induced prestin burst in the blood after cyclodextrin exposure

Abstract: In the clinical realm, we primarily rely on audiological measures for diagnosis and surveillance of sensorineural hearing loss (SNHL) and have limited therapeutic options. We have proposed a blood-based biomarker approach to overcome this challenge by measuring the outer hair cell’s (OHC) electromotile protein, prestin, in the blood. In a guinea pig model of cyclodextrin (CDX) ototoxicity, using western blots, we show that prestin in the blood may have several different forms and specifically the ~ 134 kDa for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…Western Blot Using Different Antibodies Raised to Two Different Targets Within the Prestin Molecule Confirm a 134-kDa CDX-Induced Band The apparent molecular weight of the CDX-responsive serum prestin peak is ~134 kDa (6), which is larger than the apparent molecular weight that is predicted for fulllength human prestin, which is ~81.4 kDa (8). Automated Western systems generally result in apparent molecular weights that are larger than what is predicted or found using standard Western blotting (9), which still does not account for the large difference between 81 and 134 kDa.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…Western Blot Using Different Antibodies Raised to Two Different Targets Within the Prestin Molecule Confirm a 134-kDa CDX-Induced Band The apparent molecular weight of the CDX-responsive serum prestin peak is ~134 kDa (6), which is larger than the apparent molecular weight that is predicted for fulllength human prestin, which is ~81.4 kDa (8). Automated Western systems generally result in apparent molecular weights that are larger than what is predicted or found using standard Western blotting (9), which still does not account for the large difference between 81 and 134 kDa.…”
Section: Resultsmentioning
confidence: 94%
“…Most of the above reports used the enzyme-linked immunosorbent assay technique, which cannot distinguish between prestin fragments, monomers, or multimers. Recently, we used an automated Western blot approach to determine if the characteristics of prestin differed before and after exposure to an ototoxin (6).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…By using a sandwich enzyme-linked immunosorbent assay (ELISA), Prestin was detected in the bloodstream of humans [13][14][15], rats [16,17], guinea pigs [18,19], and mice [20]. Several reports suggested that Prestin in the bloodstream could be used as a biomarker for hearing loss such as idiopathic sudden sensorineural hearing loss [13-15, 21, 22], noise-induced hearing loss [16,17,[23][24][25], sensory hearing loss [26][27][28], age-related hearing loss [29], ototoxic regents induced hearing loss, such as HPβCD [30] and cisplatin [18][19][20]31], and also hearing loss observed in various diseases like Meniere's Disease and Vestibular Migraine [32], COVID-19 [33], lead poison [34], and even surgical related damage [21]. However, the data reported in several studies lack proper negative controls and show inconsistency [13,14].…”
Section: Introductionmentioning
confidence: 99%